Novel numerical approach toward hybrid nanofluid flow subject to Lorentz force and homogenous/heterogeneous chemical reaction across coaxial cylinders - Janjua, Khuram Hina; Bilal, Muhammad; Riaz, Muhammad Bilal; Saqib, Abdul Baseer; Ismail, Emad A. A.; Awwad, Fuad A. (AIP advances, 2024)
The combination of AA7075 and Ti6Al4V aluminum alloys provides an effective balance of endurance, corrosion resistance, and lightness. Some potential applications include aviation components, marine structures with anti-corrosion characteristics, surgical instruments, and athletic apparel. Therefore, the hybrid nanofluid (Hnf) consists of aluminum alloys (AA7075-Ti6Al4V), water (50%), and ethylene glycol (EG-50%) in the current analysis. The Hnf flow subject to heat radiation and Lorentz force is studied through coaxial cylinders. In addition, the flow has been observed under the impacts of homogeneous-heterogeneous (HH) chemical reaction and exponential heat source/sink. The modeled equations (continuity, momentum, HH, and heat equations) are renovated into the non-dimensional form through the similarity approach, which are further numerically computed by employing the ND-solve technique coupling with the shooting method. It can be noticed from the graphical results that the flow rate of Hnf drops with the rising effect of porosity and magnetic field parameters. The addition of AA7075-Ti6Al4V nanoparticles (NPs) also reduces the fluid temperature and velocity profile. Furthermore, the concentration distribution diminishes with the flourishing effect of HH parameters.